Evaluation of 2 Commercially Systems for Detection of Serum Squamous Cell Carcinoma Antigen in Pan Squamous Cell Carcinoma. (23rd December 2020) - Chen, Hao; Tian, Liru; Chen, Jiahong; Sun, Peng; Han, Runkun; Wu, Xingping; Dai, Shuqin
Background: This study compared the analytical performance of the Elecsys 602 (Roche Diagnostics) system with the I2000 (Abbott laboratories) system for the quantitative measurement of squamous cell carcinoma antigen (SCCA) to assess its role as an indicator in pan squamous cell carcinoma. Methods: 435 serum samples included pan squamous cell cancer group (n = 318) and healthy subjects (n = 52) and non-squamous cell group (n = 41) and benign diseases group (n = 24) were measured by 2 systems and compared. Results: The within-run precision coefficient of variation (CV) for Abbott and Roche systems were 3.34-4.88% and 0.95 -1.96%, and the total precision CV were 2.89-9.48% and 3.97-5.38%, respectively. Good correlation was showed in Abbott and Roche systems (slopes = 0.749, r = 0.9658). Serum SCCA in the groups of nasopharyngeal carcinomas, lung squamous cell carcinoma, esophageal squamous cell carcinoma, bladder cancer and cervical squamous cell carcinoma under the curve area (AUC) was more than 0.5, while the AUC in the non- nasopharyngeal carcinomas head and neck squamous cell carcinoma was less than 0.5. The AUC of 2 systems was statistically different in lung squamous cell carcinoma and nasopharyngeal carcinomas (P < 0.05). The levels of SCCA of 2 systems were similarities in esophageal squamous cell carcinoma(stage IV vs. stage 0a-II)and bladder cancer(stage I vs. stage Oa)and cervical squamous cell carcinoma(stage IIB-III vs. stage I-IIA), which advanced stage had higher level of SCCA than early stage. But the SCCA levels of 2 systems were inconsistent in bladder cancer (stage II-IV vs. stage Oa in Abbott), head and neck squamous cell carcinoma (stage IV vs. stage Oa-I in the Roche) and lung squamous cell carcinoma (stage III vs. stage I-II in the Roche). (P < 0.05) Conclusions: 2 systems correlated well in SCCA detection of squamous cell carcinoma, but there were individual differences. Serum SCCA may also contribute to the diagnosis of bladder cancer.